2018
DOI: 10.1002/nafm.10224
|View full text |Cite
|
Sign up to set email alerts
|

Response of Riparian Vegetation, Instream Habitat, and Aquatic Biota to Riparian Grazing Exclosures

Abstract: Improper riparian grazing can alter riparian vegetation and reduce streambank stability, negatively impacting aquatic habitat and biota. We evaluated differences in riparian and instream habitat, benthic macroinvertebrates, and fish inside versus outside seven riparian exclosures constructed from 1982 to 2005 in Idaho. The normalized difference vegetation index from Landsat imagery (1985 to 2015) showed significant increases in riparian vegetation productivity after some but not all exclosures were constructed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 43 publications
0
23
0
1
Order By: Relevance
“…Prior research has elucidated relationships between grazing management, beaver, climate, and stream characteristics individually or in tandem relative to riparian area productivity in arid and semi-arid landscapes. For example, Huntington and others [48] described the correlation between climate and riparian vegetation vigor measured as NDVI, while multiple studies have demonstrated recovery of willow and other riparian vegetation with exclosure or alternative management of livestock grazing [73, 9699], including in adjacent watersheds [53, 100, 101]. Similarly, an increasing body of literature describes the anticipated riparian area benefits associated with beaver activity and identifies those physical and biological site conditions conducive to extensive beaver dam development [3747, 87].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior research has elucidated relationships between grazing management, beaver, climate, and stream characteristics individually or in tandem relative to riparian area productivity in arid and semi-arid landscapes. For example, Huntington and others [48] described the correlation between climate and riparian vegetation vigor measured as NDVI, while multiple studies have demonstrated recovery of willow and other riparian vegetation with exclosure or alternative management of livestock grazing [73, 9699], including in adjacent watersheds [53, 100, 101]. Similarly, an increasing body of literature describes the anticipated riparian area benefits associated with beaver activity and identifies those physical and biological site conditions conducive to extensive beaver dam development [3747, 87].…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrate that grazing management within exclosures can yield riparian area vegetation productivity comparable to those produced by conservation-oriented grazing management, and that beaver dams can increase the recovery effects of each of these grazing strategies, but other considerations may dictate which treatment land managers apply to meet riparian objectives. In practice, conservation-oriented grazing strategies may be preferable to exclosures due to ease of implementation, flexibility, and scale of impact [28, 100]. We acknowledge that our categorization of grazing management into three treatments may be overly simplistic but chose general categories to facilitate comparison across watersheds and time.…”
Section: Discussionmentioning
confidence: 99%
“…First, riparian vegetation can act as a buffer preventing nutrient loads from non-point sources via agricultural and urban surface runoff. The consolidation of riparian buffers (permanently vegetated areas between rivers and the surrounding landscape) is among the nutrient mitigation best management practices (Dauwalter et al, 2018;Krzeminska et al, 2019), also in the context of restoration initiatives (McMillan et al, 2014;Johnson et al, 2016). Second, the lateral hydrological connectivity between riparian areas and the main channel can stimulate riparian biogeochemical processes that can reduce nutrient loads transported downstream (Reckendorfer et al, 2013;Vigiak et al, 2016;Covino, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Landsat satellite imagery has proven to be an effective and efficient data source for monitoring key ecological attributes of meadows and riparian systems over extensive areas and time periods (Ager & Owens, ; Cartwright & Johnson, ; Cohen & Goward, ), including above‐ground biomass, which relates to vegetation structure, function and composition, and vegetation water content. Recent advances in cloud computing (Gorelick et al, ) now permit efficient application of algorithms across the Landsat satellite image archive for long‐term monitoring of groundwater dependent ecosystems with respect to climate and management (Dauwalter, Fesenmyer, Miller, & Porter, ; Hausner et al, ; Huntington et al, ).…”
Section: Introductionmentioning
confidence: 99%